„Ostatniej nocy w Soho” a tradycja włoskiego kina grozy - Michał Mazgaj (Literatura i Kultura Popularna, 2024)
This article presents and interpretation of Edgar Wright’s Last Night in Soho as an attempt to both pay tribute and offer a polemic with the tradition of Italian horror cinema, including giallo films. This approach seems valid, since one of lead actresses, Thomasin McKenzie, mentioned that during her preparations she had been told to watch a number of films, including Dario Argento’s Suspiria, one of the better-known Italian horror films.